PEDAGOGICAL-PSYCHOLOGICAL CHARACTERISTICS OF THE DEVELOPMENT OF ECONOMIC COMPETENCES OF FUTURE TEACHERS - Yorkinoy Khakimova (The Bioscan, 2024)
The term “professional competence” began to be actively used in the 90s of the last century, and the concept itself became the subject of a special, comprehensive study by many researchers dealing with the problems of pedagogical activity.